2003
DOI: 10.1007/s10329-002-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vocalizers by pant hoots, pant grunts and screams in a chimpanzee

Abstract: Identification of vocalizers was examined using an auditory-visual matching-to-sample task with a female chimpanzee. She succeeded in selecting the picture of the vocalizer in response to various types of vocalizations: pant hoots, pant grunts, and screams. When pant hoots by two chimpanzees were presented as a "duet", she could identify both of the vocalizers. These results suggest that researchers have underestimated the capability of vocalizer identification in chimpanzees. The chimpanzee correctly chose he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 18 publications
7
60
1
1
Order By: Relevance
“…Nonhuman primates can process audiovisual information cross-modally to match indexical cues (20) and number of vocalizers (21), to match and tally quantity across senses (22) and associate the sound of different call types with images of conspecifics and heterospecifics producing these calls (23)(24)(25). Research aimed specifically at investigating the categorization of individuals has shown that hamsters (Mesocricetus auratus) are capable of matching multiple scent cues to the same individual (26) and that certain highly enculturated chimps (Pan troglodytes) can, through intensive training, learn to associate calls from known individuals with images of those individuals (27)(28)(29). Some species have also been shown to spontaneously integrate auditory and visual identity cues from their one highly familiar human caretaker during interspecific, lab-based trials (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Nonhuman primates can process audiovisual information cross-modally to match indexical cues (20) and number of vocalizers (21), to match and tally quantity across senses (22) and associate the sound of different call types with images of conspecifics and heterospecifics producing these calls (23)(24)(25). Research aimed specifically at investigating the categorization of individuals has shown that hamsters (Mesocricetus auratus) are capable of matching multiple scent cues to the same individual (26) and that certain highly enculturated chimps (Pan troglodytes) can, through intensive training, learn to associate calls from known individuals with images of those individuals (27)(28)(29). Some species have also been shown to spontaneously integrate auditory and visual identity cues from their one highly familiar human caretaker during interspecific, lab-based trials (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The relative complexity of this process explains why individual recognition has long been thought to be a uniquely human capacity, which has been reported to develop ∼4 mo of age (35). However, it has recently been demonstrated in a few other species (16)(17)(18)(19) and might be more widespread in animals (36,37). Evidence for individual recognition by rhesus macaques raises the issue of the adaptive value of this very precise type of social recognition during interactions with conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have applied this approach to investigate individual recognition in species other than humans and chimpanzees (16,17) and none of them focused on rhesus monkeys. Moreover, these studies explored individual recognition of peers (18,19), but did not examine whether this capacity extended to other species.…”
mentioning
confidence: 99%
“…Subsequent playbacks showed mother macaques were sensitive to this information conveyed in their offspring's screams, responding most strongly to screams that indicated a high risk of physical harm to her infant or a threat to the matrilineal dominance hierarchy (Gouzoules et al 1984). Although there is evidence that screams carry fewer identity cues than other more tonal call types (Owren and Rendall 2003), Cheney and Seyfarth (1980) showed that vervet monkeys can make judgements about caller identity from screams; a finding replicated in rhesus macaques (Gouzoules et al 1986;Fugate et al 2008), Barbary macaques (Fischer 2004) and captive chimpanzees (Kojima et al 2003).…”
Section: Introductionmentioning
confidence: 98%